2019
DOI: 10.1109/tdei.2019.008052
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of partial discharge induced by continuous X-ray exposure of void defects in insulator

Abstract: Partial discharge (PD) diagnosis is a part of a routine testing of solid insulating materials to detect void defects. However, the conventional diagnosis is prone to inception delays due to lack of initiatory electron production, especially inside small voids. In this study, we employed continuous irradiation of X-rays to induce and sustain discharge inside the voids. The PD characteristics of void samples under different exposure rates of X-rays were observed. Compared with the conventional diagnosis, this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The ion drift-diffusion simulation model based on the fluid equation has also been introduced to estimate void PDIE by previous scholars [6,13,14]; their simulation results were in close accordance with theoretical predictions, which suggests that these methods can be used to estimate void PDIE. The PDIE obtained via model experiment under the same void parameters, however, deviates significantly from the results obtained by the above two methods; the measured value may be several times higher than the theoretical value [15]. There are also significant differences in test results among various researchers, even under the same conditions.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…The ion drift-diffusion simulation model based on the fluid equation has also been introduced to estimate void PDIE by previous scholars [6,13,14]; their simulation results were in close accordance with theoretical predictions, which suggests that these methods can be used to estimate void PDIE. The PDIE obtained via model experiment under the same void parameters, however, deviates significantly from the results obtained by the above two methods; the measured value may be several times higher than the theoretical value [15]. There are also significant differences in test results among various researchers, even under the same conditions.…”
Section: Introductionmentioning
confidence: 56%
“…shown that increasing background radiation can significantly raise the probability of PD within the voids [15,30,36]. Figure 10 shows the PDIV of voids with and without x-ray irradiation, where x-ray irradiation did significantly reduce PDIV and its dispersion.…”
Section: Effect Of Background Radiation Previous Studies Havementioning
confidence: 98%
See 1 more Smart Citation